1983
DOI: 10.1590/s0004-282x1983000200001
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulações linfocitarias do liquido cefalorraqueano normal: I. principais registros da literatura

Abstract: Data concerning the characterization of lymphocytes in the cerebrospinal fluid are reviewed, markedly those on T and B subpopulations. Special attention is given to T-lymphocyte subpopulations actually related to the immune response and to the immune regulation within the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…However, these uncommon pancreatic malignancies displayed completely different molecular profiles and clinical outcomes from those of classical PDAC. This suggested that inclusion of such tumours in the training set can lead to inaccurate conclusions about prognostic performance [ 31 ]. To avoid repeating this mistake, non-PDAC samples were strictly filtered out in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, these uncommon pancreatic malignancies displayed completely different molecular profiles and clinical outcomes from those of classical PDAC. This suggested that inclusion of such tumours in the training set can lead to inaccurate conclusions about prognostic performance [ 31 ]. To avoid repeating this mistake, non-PDAC samples were strictly filtered out in the current study.…”
Section: Discussionmentioning
confidence: 99%